Metabólitos secundários obtidos de Diaporthe sp. aplicados para o controle de plantas daninhas - Pes, Maiquel Pizzuti (2015)
Weed plants are currently one of the main factors to restrain crop yield worldwide. The mycoherbicides are considered an important alternative to aim weed plants management, because of its efficiency of control and low environmental impact. The aim of the present study was to evaluate the herbicidal effect of secondary metabolites of the fungus Diaporthe sp. isolated from Solanum americanum plant to the control of different species of weeds and crops. In this sense, bioassays were carried with pre-emergence application (primary assessment) and post-emergency aplication (secondary assessment) plants in laboratory and greenhouse. Secondary metabolites were obtained through a process of submerged fermentation in a benchtop bioreactor. Assessment was carried out in the laboratory by means of germination tests on seeds for the species Glycine max, Cucumis sativus, Sorghum halepense, Oryza sativa, Triticum aestivum and Lolium multiflorum. To this, polyethylene boxes were used, which contained germitest role as substrate, previously soaked in 10 mL of secondary metabolites. In each box were equidistantly allocated 25 seeds, and right after capped and sealed with parafilm and taken to a germination chamber for a period of seven days. As for the secondary assessment two experiments were carried in a greenhouse. Experiment 1 was composed by applying different doses of secondary metabolites (0, 1 / 4D 1 / 2D, D, 2D, 4D and 8D) on the aerial part of the plants species Glycine max, Conyza sp., Oryza sativa, Echinochloa sp., Triticum aestivum and Lolium multiflorum. To the experiment 2 these same plant species were used. However, the treatments consisted of mix between commercial herbicides and secondary metabolites to assess a possible synergism caused by the mixture of the compounds. In addition, an adjuvant was added together with the secondary metabolites to verify any improvement on the herbicide effect. For both experiments were evaluated the dry mass weight of the aerial part, phytotoxicity and control efficiency. The results obtained in the primary evaluation demonstrated that the secondary metabolites applied at pre emergency inhibited germination for the species used in the study at a rate of 100%. On the secondary assessment for the experiment 1, the highest dose resulted in a weight reduction of plants aerial dry mass for the species Glycine max and Conyza sp. At Experiment 2 no synergism was found for the mixture of secondary metabolites and commercial herbicides to any of the plant species. The addition of an adjuvant to secondary metabolites resulted in better action against the species Glycine max, Echinochloa sp. and Lolium multiflorum.